4C Competencies of Laboratory Assistants: A Catalyst for Improved Experimental Comprehension in Physics Education - Agustina, Rena Denya; Putra, Riki Purnama; Chusni, Muhammad Minan; Siregar, Zulli Umri; Wahyudi, Dedi (Yayasan Nurul Yakin Bunga Tanjung, 2025)
This study addresses a pressing issue in physics education: the underutilization of laboratory assistants as facilitators of conceptual learning, particularly in experimental settings. Despite their vital role, the impact of their 21st-century competencies, known as the 4C skills, on students' experimental comprehension remains underexplored. This study investigates the influence of laboratory assistants' 4C competencies on Students' Experimental Comprehension (SEC) in Basic Physics Practicum I and II at the Physics Education Study Program, UIN Sunan Gunung Djati Bandung. Employing a quantitative quasi-experimental approach, data were collected from 29 laboratory assistants and 401 students between 2020 and 2024. Validated instruments, including written tests, structured observation sheets, and documentation of practicum results, ensured methodological rigor. Multiple linear regression analysis revealed that the 4C competencies significantly predicted SEC (R² = 0.869), with creativity (β = 0.461) and critical thinking (β = 0.350) emerging as the most influential dimensions. Pearson correlation further confirmed strong positive relationships between each competency and SEC. The findings highlight the critical role of soft skills in laboratory-based science education, suggesting that structured training in 4C competencies can substantially enhance experimental learning outcomes. This research offers new insights for curriculum developers, educational policymakers, and laboratory supervisors who aim to strengthen practicum quality by empowering laboratory assistants as active pedagogical agents.